Impact of Organisational Climate on Managerial Effectiveness - Lehal, Ritu (Gyan Management Journal, 2007)
Organisational Climate can directly influence the performance of employees working in any organisation. This impact has been studies in context Of 120 executives of three major units of  Electronics Industry in Punjab . Speannan 's rank correlation test indicates that there is a positive relation between the two variables. The results of 'multiple regressio n analysis' explain that out of 15 sub- factor s of Organisation Climate, standards and decision makin g are two factors which have significant but negative relationshi p with Managerial Effectiveness. On the other hand warmth, Initiative and Risk have also great influence on Managerial Effectiveness.
Keywords: Organisational Climate; Managerial Effectiveness; organisation